2022
DOI: 10.21512/lc.v16i1.7764
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogic Interaction in an Online EFL Class at a Junior High School in Depok

Abstract: The research was conducted to investigate how the teacher built pedagogic interactions with the students in an online EFL class in Depok, including how the teacher used speech structures, language shifts, and how the students perceived the interactions. The shift to online learning in the pandemic era had affected the quality of learning. Due to the complexity of online learning, interpersonal interactions between teachers and students were frequently overlooked in an online class. Applying exploratory sequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
3
1
0
Order By: Relevance
“…In addition, this study's findings regarding the usefulness of Grammarly in checking various grammatical-related issues are in accord with recent studies of, for example, Miranty and Widiati (2021) and Hakiki (2021). This current study found that the students favored Grammarly for its constructive feedback pertaining to stylistic issues; hence, it is consistent with data obtained in earlier investigations Dewi (2022) and Lailika (2019). The students in this study and those in previous research (Hakiki, 2021;Pratama, 2021) felt that Grammarly boosted their confidence and motivation in writing academic work.…”
Section: Handy and Practical Usesupporting
confidence: 92%
See 3 more Smart Citations
“…In addition, this study's findings regarding the usefulness of Grammarly in checking various grammatical-related issues are in accord with recent studies of, for example, Miranty and Widiati (2021) and Hakiki (2021). This current study found that the students favored Grammarly for its constructive feedback pertaining to stylistic issues; hence, it is consistent with data obtained in earlier investigations Dewi (2022) and Lailika (2019). The students in this study and those in previous research (Hakiki, 2021;Pratama, 2021) felt that Grammarly boosted their confidence and motivation in writing academic work.…”
Section: Handy and Practical Usesupporting
confidence: 92%
“…The study found that representing the indicator of perception -a perceived object, Grammarly was deemed to offer hands-on uses. The finding of this study that Grammarly is deemed to be handy for students to deal with wide-ranging grammatical issues in their academic writing is in line with those of Hakiki (2021) and Dewi (2022). The students in this study and those in the studies of Dewi (2022) and Miranty and Widiati (2021) agree with Grammarly's reliable constructive feedback provisions.…”
Section: Handy and Practical Usesupporting
confidence: 68%
See 2 more Smart Citations